Radiographic Predictors for Adverse Outcomes Following Surgical Correction of Hammertoe Deformity. Issue 4 (16th October 2019) - Maidman, Samuel D.; Erwood, Amalie A.; Brodsky, James; Daoud, Yahya; Fantry, Amanda; Tenenbaum, Shay; Bariteau, Jason T.
Category: Lesser Toes Introduction/Purpose: Hammertoe deformities are common, often painful deformities of the lesser foot and are known to severely affect physical function. When patients seek surgical management, x-ray imagining is utilized for diagnosis, evaluation for surgical candidacy, and selection of the operative technique. Postoperatively, radiographs are retaken to assess bone health, healing status, and alignment. Despite their frequent use, no previous data support particular X-ray findings as being indicative of clinical presentation nor surgical outcomes. The aim of this study is to identify specific radiographic parameters that are predictive of pain and function outcomes after surgical correction of hammertoe deformity. Methods: Prospectively collected data was reviewed on 116 patients who underwent hammertoe correctional surgery. Patient demographics, comorbidities, and postsurgical complications were recorded from their electronic medical records. Clinical outcomes were assessed utilizing preoperative and postoperative pain Visual Analogue Scale (VAS) and Short Form Health Survey Physical Component (SF-36 PCS) scores with 1-year follow-up. Radiographs were scored by a foot & ankle fellowship-trained orthopaedic surgeon to assess preoperative severity, postoperative joint fusion, and both pre- and postoperative joint instability. Data was examined using chi-squared, t-test, and ANOVA analyses. Results: Preoperatively, 14.7% of patients had a deformity classified radiographically as mild, 37.1% as moderate, and 48.3% as severe. X-rays prior to surgery showed that 65.5% had MTP joint instability, 9.5% had joint dislocation, and 18.1% had joint arthritis. Postoperatively, 78.5% had PIP joint fusion, 38.8% had MTP joint arthritis, and 17.2% had MTP joint instability. A significant association was found between postoperative MTP joint instability and a lower 1-year SF-36 PCS (p=0.0032). There were no associations found between the other radiographic findings and postoperative outcomes, and no parameters were associated with pain VAS scores. Conclusion: After undergoing surgical correction of hammertoe deformity, the postoperative radiographic finding of MTP joint instability was determined to be predictive of physical function. However, neither metatarsophalangeal joint arthritis nor PIP fusion were predictive of outcomes. This work informs foot and ankle specialists that proper joint alignment and stabilization is critical to ensuring success in hammertoe surgery.